Factors Related to Health Promoting Behaviors for Breastfeeding Among Mothers with Gestational Diabetes Mellitus - Injan, Wimolsiri; Prasitwattanaseree, Piyaporn; Sriarporn, Punpilai (NU Journal of Nursing and Health Sciences, 2025)
Postpartum mothers with gestational diabetes mellitus continue to experience insulin resistance and inappropriate health-promoting behaviors, affecting maternal health and breastfeeding. The purpose of this descriptive correlational research study was to describe the relationship between perceived benefits of breastfeeding, perceived insufficient milk supply, perceived self-efficacy of breastfeeding, and health-promoting behaviors for breastfeeding among mothers with gestational diabetes mellitus. The 134 participants consisted of postpartum mothers with gestational diabetes mellitus at 4-6 weeks who went for check-up at the family planning unit of Maharaj Nakorn Chiang Mai Hospital and Health Promotion Center First Region Chiang Mai between June 2023 to November 2023. The research instruments included demographic questionnaire, the Health Promoting Behaviors for Breastfeeding Among Mothers with Gestational Diabetes Questionnaire, the Perceived Benefits of Breastfeeding Among Mothers with Gestational Diabetes Questionnaire, the Hill & Humenick Lactation Scale, and the Breastfeeding Self-Efficacy Scale-Short Form with reliability .89, .81, .92 and .93 respectively. The data were analyzed using descriptive statistics, Pearson’s product moment correlation, and Spearman rank correlation coefficient statistics.The results showed that perceived benefits of breastfeeding, perceived insufficient milk supply and perceived self-efficacy of breastfeeding had a significant positive correlation with health promotion behavior for breastfeeding (r = .432, r = .390 and r = .401, p < .001 respectively).This research suggests that midwives should promote perceived benefits of breastfeeding, and perceived self-efficacy of breastfeeding, but reduce perceived insufficient milk supply for mothers with gestational diabetes mellitus. To help mothers establish the appropriate health-promoting behaviors for breastfeeding.